An audit to assess the impact of prescribing a monofilament fibre debridement pad for patients with unhealed wounds after six months. (2nd May 2021) - Burnett, Joanna; Kerr, Andrew; Morrison, Margaret; Ruston, Abbe
Abstract : A monofilament fibre debridement pad has been found to be a rapid and effective mechanical method of removing dry skin, biofilm and debris from acute and chronic wounds with minimal patient discomfort. Evidence of its impact on prescribing and wound healing, however, has been more limited. The aim of this audit was to show evidence of the monofilament fibre debridement pad's impact on wound treatment costs through an analysis of NHS wound-care prescribing data in England. A dataset for 486 uniquely identified patients who had been newly prescribed the monofilament fibre debridement pad was obtained from the NHS Business Services Authority. All data were anonymised. Costs were identified for the six months before and six months after the month of first prescription of the monofilament fibre debridement pad. The total cost of wound-care prescribing fell by 14% or £101, 723 in the six months after the intervention compared with the six months before. The average monthly expenditure per patient fell from £244 before the intervention to £209 (n=486) after. These results indicate that use of the monofilament fibre debridement pad could reduce prescribing costs and the use of antimicrobial and negative pressure therapies. Further research is warranted to investigate the clinical role of the monofilament fibre debridement pad in wound healing